Mucormycosis of oral cavity: a descriptive case report from a tertiary care hospital - Kumar, Binay; Prasad, Nidhi (International Journal of Research in Medical Sciences, 2022)
We presented an interesting case report of mucormycosis (Rhizopus Oryzae) in a recovered COVID-19 patient, its diagnosis and identification. The patient in past visited our institute with symptoms of COVID-19, she was a known case of tuberculosis and was taking ATT and diabetic (DM-2) patient. She was diagnosed COVID positive and successfully treated at our institution and discharged after recovering from the complications. After approximately two months of getting discharged from the hospital she again visited the post COVID clinic with symptoms of fever and numbness around face and on routine examination a blackish tissue like growth seen involving the hard palate and post nasal area. Mucormycosis (phycomycosis, zygomycosis) is an acute opportunistic infection generally develops secondary to debilitating diseases. But increased incidence was noticed in COVID-19 affected individuals. In head, neck and oral cavity the mold usually gains entry through respiratory route involving maxillary sinuses and oral cavity. The fungus causes great damage to the anatomical structures leading its necrosis. Hence an early diagnosis and surgical interventions is must for a good prognosis, decreasing morbidity and mortality. Extensive Research needs to be carried out in COVID patient specially treatment to prevent and reduce the cases of opportunistic infection in order to reduce its incidence and morbidity/mortality.